Comparison of crops raised with tissue culture vis-a-vis conventional seed tubers of potato - MURLIDHAR J. SADAWARTI; A.K. SOMANI; Y.P. SINGH; K.K. PANDEY (Seed Research, 2026)
An attempt was made to compare stage-III and stage-IV seed crops (conventional tubers) with their respective counterpart's generation-1 and generation-2 seed crops (tissue culture tubers) in Kufri Sindhuri, Kufri Lauvkar and Kufri Chandramukhi in factorial RBD replicated three times during 2010-11 and 2011-12. For morphological parameters, there were no significant differences among respective counterparts respectively. In case of yield parameters, generation-1 (8, 19,000) and generation- 2 (7, 42,000) recorded significantly higher tuber number over their respective counterpart stage-III (5, 96,000) and stage-IV (6, 53,000) respectively. For tuber weight (t/ha) there was no significant difference among the respective counterparts. ELISA testing results revealed that generation-1 (1.11%) and generation-2 (1.83%) recorded significantly lower disease percent over their respective counterpart's stage-III (3.33%) and stage-IV (4.33%). The hi-tech seed tubers were better than conventional seed tubers health wise and can be integrated with conventional system for breeder seed production.